2006
DOI: 10.1038/sj.ki.5001930
|View full text |Cite
|
Sign up to set email alerts
|

Patient and technique survival on peritoneal dialysis in patients with failed renal allograft: A case–control study

Abstract: Failed renal allograft is becoming one of the most frequent causes of dialysis initiation in countries with developed transplant programs. The majority of patients initiate hemodialysis (HD) as their next renal replacement modality and concerns about the success of peritoneal dialysis (PD) in this patient population has been expressed. We evaluated patient and technique outcome in a cohort of 494 patients in the United States who initiated PD after a failed renal allograft in the years 2000-2003, and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 24 publications
2
27
1
2
Order By: Relevance
“…The survival of DAGL patients has primarily been examined in hemodialysis (HD)-treated patients, and few studies have specifically examined the impact of dialysis modality on survival in this patient population. Intriguingly, a few studies have shown favorable outcomes in peritoneal dialysis (PD)-treated DAGL patients (17)(18)(19). Badve et al (18) studied patients initiating PD after transplant failure in Australia and New Zealand between 1991 and 1994.…”
Section: Introductionmentioning
confidence: 99%
“…The survival of DAGL patients has primarily been examined in hemodialysis (HD)-treated patients, and few studies have specifically examined the impact of dialysis modality on survival in this patient population. Intriguingly, a few studies have shown favorable outcomes in peritoneal dialysis (PD)-treated DAGL patients (17)(18)(19). Badve et al (18) studied patients initiating PD after transplant failure in Australia and New Zealand between 1991 and 1994.…”
Section: Introductionmentioning
confidence: 99%
“…Bu konuda yapılmış en büyük çalışmada 494 nakledilmiş böbreğini kaybetmiş PD hastası, 491 yeni PD hastası ve 479 HD'den PD'e dönüş yapan hasta karşılaştırılmıştır (15). Sonuçta teknik sağkalım ve mortalite açısından her üç hasta grubu arasında anlamlı bir fark saptanmamıştır; ancak bu seride de immün sistemi baskılanmış olan hastalarda daha yüksek oranda peritonit görülmüştür.…”
Section: Allograft Kaybı Sonrasında Uygun Renal Replasman Tedavisininunclassified
“…Une reprise plus précoce de la fonction du greffon est de plus en plus discutée en raison d'un moindre état d'inflation hydrosodée, facteur a priori favorable, des patients en DP depuis l'utilisation des solutions plus biocompatibles (icodextrine) et d'un maintien du patient hémodialysé au-dessus de son poids sec en cas de séance d'épuration en préopératoire [25]. La prise en charge en DP après échec de transplantation rénale est possible [26].…”
Section: Utilisation Croissante De Solutions Plus Biocompatiblesunclassified